2020
DOI: 10.1093/cvr/cvaa033
|View full text |Cite
|
Sign up to set email alerts
|

Junctophilin-2 tethers T-tubules and recruits functional L-type calcium channels to lipid rafts in adult cardiomyocytes

Abstract: Aim In cardiomyocytes, transverse tubules (T-tubules) associate with the sarcoplasmic reticulum (SR), forming junctional membrane complexes (JMCs) where L-type calcium channels (LTCCs) are juxtaposed to Ryanodine receptors (RyR). Junctophilin-2 (JPH2) supports the assembly of JMCs by tethering T-tubules to the SR membrane. T-tubule remodelling in cardiac diseases is associated with downregulation of JPH2 expression suggesting that JPH2 plays a crucial role in T-tubule stability. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 68 publications
(77 reference statements)
4
25
0
Order By: Relevance
“…Data in Figure 1 were also confirmed by images in Figure 2, where we immunolabeled the external membranes (i.e., T-tubule) using WGA (Figure 2A,D) [37] and antibodies against Cav-3 (Figure 2B,E) [38] and JP-2 (Figure 2C,F) [38]. Cav-3 is a protein that plays a key role in T-tubulation, whereas JP-2 is a membrane bridging protein which supports the assembly of junctional membrane complexes by tethering T-tubules to the Double-immunolabeling with primary antibodies against RYR2 and TOM20 revealed that in adult cardiomyocytes (a) the EC coupling apparatus has an ordered transversal disposition that creates a cross-striated pattern (Figure 1A; red labeling) while (b) mitochondria are mainly disposed longitudinally between the myofibrils (Figure 1A; green labeling).…”
Section: Ageing Causes Disarray Of Mitochondrial and Ec Coupling Systemssupporting
confidence: 72%
See 3 more Smart Citations
“…Data in Figure 1 were also confirmed by images in Figure 2, where we immunolabeled the external membranes (i.e., T-tubule) using WGA (Figure 2A,D) [37] and antibodies against Cav-3 (Figure 2B,E) [38] and JP-2 (Figure 2C,F) [38]. Cav-3 is a protein that plays a key role in T-tubulation, whereas JP-2 is a membrane bridging protein which supports the assembly of junctional membrane complexes by tethering T-tubules to the Double-immunolabeling with primary antibodies against RYR2 and TOM20 revealed that in adult cardiomyocytes (a) the EC coupling apparatus has an ordered transversal disposition that creates a cross-striated pattern (Figure 1A; red labeling) while (b) mitochondria are mainly disposed longitudinally between the myofibrils (Figure 1A; green labeling).…”
Section: Ageing Causes Disarray Of Mitochondrial and Ec Coupling Systemssupporting
confidence: 72%
“…Data in Figure 1 were also confirmed by images in Figure 2, where we immunolabeled the external membranes (i.e., T-tubule) using WGA (Figure 2A,D) [37] and antibodies against Cav-3 (Figure 2B,E) [38] and JP-2 (Figure 2C,F) [38]. Cav-3 is a protein that plays a key role in T-tubulation, whereas JP-2 is a membrane bridging protein which supports the assembly of junctional membrane complexes by tethering T-tubules to the SR membrane [37,38]: in aged cardiomyocytes the transversal labeling is frequently interrupted by longitudinally oriented fluorescence, indicative of a loos of integrity and organization of the sarcotubular system. By WB we also evaluated the expression levels of either JP-2 or Cav-3 and verified that both were reduced in samples from aged mice (Figure 2G,H), providing a possible molecular mechanism underlying the age-related disarray of the T-tubule network.…”
Section: Ageing Causes Disarray Of Mitochondrial and Ec Coupling Systemssupporting
confidence: 72%
See 2 more Smart Citations
“…An interesting avenue for future research in those topics is that of the role of the junctional tethering protein junctophilin 2 (JPH2) in targeting Ca V 1.2 to microdomains within the sarcolemma. A recent study reported that JPH2 recruits Ca V 1.2 to lipid rafts on the T-tubules wherein overexpression of JPH2 in cultured rat cardiomyocytes led to increased channel density at the t-tubule and surface membrane that was not accompanied by an increase in total cellular Ca V 1.2 protein, implying JPH2 increased channel trafficking rather than altered channel biosynthesis [ 143 ]. Future studies should also parse out the mechanistic details of trafficking alterations that may explain how failing hearts redistribute Ca V 1.2 from the t-tubular sarcolemma to the surface membrane [ 144 , 145 , 146 ], and others that mediate the enhanced Ca V 1.2 sarcolemmal expression observed with aging [ 147 , 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%